Unconventional monetary policy or automatic stabilizers? A financial post-Keynesian comparison - Nitin Nair (Levy Economics Institute of Bard College, 2023)
The purpose of public policy, expansionary or contractionary, is to encourage the expansion of income, output, and employment. Theory decides the nature and kind of policy, and the underlying mechanics that result in expansion. Keynes (1964) brings money and a monetary production economy to the forefront of economic analysis, yet in the General Theory, he is skeptical of the efficacy of monetary policy. This paper analyzes how prices of assets, liabilities, and commodities interact in response to unconventional monetary policy and fiscal policy (namely automatic stabilizers) to create conditions that stimulate private investment and economic activity. Modern economics, after accepting the need for intervention, tends to attempt to use monetary policy to steer aggregate demand. "Unconventional" monetary policy such as zero and negative interest rates, and quantitative easing have been instituted in an attempt to fight slumps and stimulate economic activity without increasing government deficits. In this paper, we point out- using Davidson's (1972) financial post-Keynesian framework-how unconventional monetary policy is not sufficient to create the conditions of backwardation that stimulate production. Finally, we explain how automatic stabilizers, using the Kalecki profits (price) equation, are the best avenue to create the conditions for backwardation that stimulate economic activity. We conclude, like Keynes, that fiscal policy is the reliable path to economic expansion.
Keywords: E12; E44; H50; E52; E62; 330; Financial post-Keynesian Theory; Unconventional Monetary Policy; Quantitative Easing; Automatic Stabilizers; backwardation; Contango; Tobin's Q; Paul Davidson